Improving Strategic Competence Lessons from 13 Years of War - Robinson, Linda (RAND Corporation, 2014)
Drawing lessons from the past 13 years of war, this study analyzes the future operating environment and identifies critical requirements for land forces and special operations forces to operate successfully in conjunction with joint, interagency, and multinational partners in irregular and hybrid conflicts.